Le moulage pour la reconstitution des lacunes en restauration de la céramique et du verre - Hélène Blanpain (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
The technique of gap-filling by molding is very vast. It presents a wide range of products and processes than can be used in the field of the restoration of ceramic and glass objects. Their choice depends on several factors : the material of the object, its shape, and the choice of the filling product.